Improving ESG Activity Recognition through Job Crafting: The Mediating Effect of Work Engagement and Innovative Organization Culture - Nilam Cindera Dewi S; Anggraini Sukmawati; Naufal Mahfudz (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the era of globalization, businesses face increasing challenges in achieving operational efficiency, social responsibility, and long-term sustainability. Consequently, Environmental, Social, and Governance (ESG) practices have become a strategic priority, with organizations integrating sustainability into corporate strategies and operational practices, including job crafting. This study investigates the relationship between job crafting and ESG activity recognition, while analyzing the mediating roles of work engagement and innovative organizational culture. This study employed a quantitative research approach using non-probability sampling with a purposive sampling technique based on specific criteria. The results indicate that job crafting does not have a significant direct effect on ESG activity recognition. However, work engagement is empirically proven to act as a full mediator in the relationship between job crafting and ESG activity recognition. Conversely, innovative organizational culture does not demonstrate a mediating role in this model, as its effect on ESG activity recognition is not significant. Nevertheless, job crafting contributes significantly and strongly to enhancing work engagement and building an innovative organizational culture within the company. These findings emphasize that employee pro-activity through job crafting can only optimize ESG recognition if it successfully boosts daily work engagement.